DEMOCRATIC BACKSLIDING THROUGH FAST-TRACK LEGISLATION PRACTICES: A SOCIO-POLITICAL STUDY OF THE EROSION OF DEMOCRATIC VALUES IN INDONESIA - Iskandar Syukur (PAPATUNG: Jurnal Ilmu Administrasi Publik, Pemerintahan dan Politik, 2025)
The development of democracy in Indonesia has shown changes in the public policymaking process, marked by the increasing use of legislative mechanisms that occur in a relatively short period of time. This situation raises concerns because the regulatory process is not only related to the need for effective governance but also relates to the relationship between the state, political institutions, and society in democratic life. Changes in the legislative process also affect the scope for public participation, power relations in decision-making, and the quality of public involvement in the political process. This study aims to analyze the practice of FAST-TRACK LEGISLATION in relation to changing political relations and its implications for the quality of democracy in Indonesia. This study uses a qualitative approach, collecting data through a literature review obtained from various sources, such as scientific articles, previous research results, books, and documents relevant to the research focus. The results indicate that the practice of FAST-TRACK LEGISLATION not only influences the regulatory formation process but also influences the patterns of relationships between actors in the policymaking process. These changes impact the scope for public participation, the level of public trust in political institutions, and the pattern of public oversight of state policies. Changes in the legislative process have implications for the quality of democracy in Indonesia because they affect the balance of relations between the state, political institutions, and society in the process of organizing national life.